Perceived potentially inappropriate treatment in the PICU: frequency, contributing factors and the distress it triggers - Sarpal, Amrita; Miller, Michael R.; Martin, Claudio M.; Sibbald, Robert W.; Speechley, Kathy N. (Frontiers in Pediatrics, 2024)
Background: Potentially inappropriate treatment in critically ill adults is associated with healthcare provider distress and burnout. Knowledge regarding perceived potentially inappropriate treatment amongst pediatric healthcare providers is limited.Objectives: Determine the frequency and factors associated with potentially inappropriate treatment in critically ill children as perceived by providers, and describe the factors that providers report contribute to the distress they experience when providing treatment perceived as potentially inappropriate.Methods: Prospective observational mixed-methods study in a single tertiary level PICU conducted between March 2 and September 14, 2018. Patients 0-17 years inclusive with: 1) ≥ 1 organ system dysfunction 2) moderate to severe mental and physical disabilities, or 3) baseline dependence on medical technology were enrolled if they remained admitted to the PICU for ≥ 48h, and were not medically fit for transfer/discharge. The frequency of perceived potentially inappropriate treatment was stratified into three groups based on degree of consensus (1, 2 or 3 providers) regarding the appropriateness of ongoing active treatment per enrolled patient.Distress was self-reported using a 100-point scale.Of 374 patients admitted during the study, 133 satisfied the inclusion-exclusion criteria.Eighteen patients (unanimous -3 patients, 2 providers -7 patients; single provider -8 patients) were perceived as receiving potentially inappropriate treatment; unanimous consensus was associated with 100% mortality on 3-month follow up post PICU discharge. Fifty-three percent of providers experienced distress secondary to providing treatment perceived as potentially inappropriate. Qualitative thematic analysis revealed five themes regarding factors associated with provider distress: 1) suffering including a sense of causing harm, 2) conflict, 3) quality of life, 4) resource utilization, and 5) uncertainty.Conclusions: While treatment perceived as potentially inappropriate was infrequent, the provider distress was commonly observed. By identifying specific factor(s) contributing to perceived potentially inappropriate treatment and any associated provider distress, organizations can design, implement and assess targeted interventions.